Reproductive Behavior of Oreochromis variabilis (Boulenger, 1906) in Small Water Bodies: A Case Study of Lake Victoria Basin, Kenya - Maithya, J.; Okeyo-Owuor, J. B.; Wangila, B. C. C. (Africa Environmental Review Journal, 2015)
Oreochromis variabilis (Boulenger), an endemic fish species to Lake Victoria, was abundant and of great economic importance in the 1950s. However, after early 1960s to this date, its catches disappeared from the lake’s fisheries; the species became extremely endangered, and is now listed in the World Conservation Union (IUCN) Red Book of endangered species. Investigations of the reproductive ecology of resilient stocks revealed that sex-related morphormetric characteristics of these stocks are useful criteria for recommending strategies for stock enhancement, restoration and conservation of O. variabilis. There was preponderance of males over females in all populations; O. variabilis reproduced throughout the year; 50% of populations reached first maturity at sizes optimal for commercial exploitation; fecundity was high. These factors, coupled with large sizes of oocytes and excellent condition factor are enough ecological criteria for recommending increased captive propagation of the species in small water bodies in the Lake Victoria Basin.